Exploring Chemical Diversity of Phorbas Sponges as a Source of Novel Lead Compounds in Drug Discovery - Alessia Caso; Fernanda Barbosa da Silva; Germana Esposito; Roberta Teta; Gerardo Della Sala; Laura P. A. Nunes Cavalcanti; Alessandra Leda Valverde; Roberto Carlos C. Martins; Valeria Costantino (Marine Drugs, 2021)
Porifera, commonly referred to as marine sponges, are acknowledged as major producers of marine natural products (MNPs). Sponges of the genus Phorbas have attracted much attention over the years. They are widespread in all continents, and several structurally unique compounds have been identified from this species. Terpenes, mainly sesterterpenoids, are the major secondary metabolites isolated from Phorbas species, even though several alkaloids and steroids have also been reported. Many of these compounds have presented interesting biological activities. Particularly, Phorbas sponges have been demonstrated to be a source of cytotoxic metabolites. In addition, MNPs exhibiting cytostatic, antimicrobial, and anti-inflammatory activities have been isolated and structurally characterized. This review provides an overview of almost 130 secondary metabolites from Phorbas sponges and their biological activities, and it covers the literature since the first study published in 1993 until November 2021, including approximately 60 records. The synthetic routes to the most interesting compounds are briefly outlined.